Dynamic Analysis of Energy Export and Helmand Rights Scenarios in Water Resources Management of Sistan Region - zahra ghaffari moghadam; ali sardarshahraki; neda aliahmadi (اکوهیدرولوژی)
Research Topic: The present study models the dynamics of the water resources management system in the Sistan region, focusing on the water-food-energy nexus.Objective: a water, food, energy system dynamic model simulation was developed, taking into account the results of Sensitivity analysis, to develop sustainable water resources policy in the form of a water demand, water supply, food resource management, and energy management.Method: The initial modeling and simulation were conducted using Vensim DSS software. The required data included surface water inflow, water delivered to the domestic and agricultural sectors, the number of agricultural wells, cultivated area and crop yields, production levels of livestock, poultry, and fisheries, as well as energy carriers for the period 2006-2036. After applying each of the water demand and supply management policies and food and energy resource management policies separately to the model, the best scenarios were selected and implemented in combination. The results were then compared with one another.Results: According to the results of the simulation model, in the scenario of electricity export in exchange for receiving water rights, water security increased by 4,920 million cubic meters, and consequently, energy security also increased by 297,504 kilowatt-hours. Moreover, implementing the scenario of eliminating water-intensive crops such as wheat and barley and replacing them with alternative crops led to an improvement in water security, and energy security increased by 692,399 kilowatt-hours compared to the base year. However, food security declined due to the complete removal of these crops from the region. Under the scenario of enforcing water rights by the neighboring country (Afghanistan), water security increased by 9,840 million cubic meters, which showed a significantly higher growth compared to the base scenario. In the scenario of reducing large livestock by 10% and increasing small livestock by 10%, water security showed no increase (remained at zero).Conclusions: Analysis of the results and data comparison trends revealed that the system dynamics modeling in the Sistan region indicates an unfavorable outlook for water resources and food production over the 30-year period. The simultaneous implementation of policies including energy export, enforcement of water rights, crop pattern reform, and livestock optimization can improve the security of water, food, and energy resources and contribute to achieving regional sustainability. These strategies, within the framework of the water-food-energy nexus approach, play a key role in integrated resource management.